Relasi “Dialektik–Etik” Islam-Demokrasi di Indonesia - Arifin, Syamsul (MAARIF Institute, 2023)
Ahmad Syafii Maarif—whose nickname is Buya Syafii—is one of the leading Muslim intellectuals in Indonesia who inherited not only scholarly work, but also an exemplary personality to which he has attached attributes as a national figure. Maarif has come up with various ideas which are spread across various publication platforms such as articles in various leading newspapers and books. Maarif is also active and has an important role in community organizations and government institutions. Maarif was the General Chair of the Muhammadiyah Central Leadership in 1998-2005 and a member of the Steering Committee of the Pancasila Ideology Advisory Board (BPIP). Maarif has also been president of the World Conference on Religion and Peace (WCRP) as a world interfaith forum in New York which promotes religion as an instrument of peace and non-violence. By considering his character and pioneering as one of the leading Muslim intellectuals and figures in Indonesia, Maarif is an interesting and important study subject. This article pays attention to Islamic thought or Maarif Islamic intellectualism which wants to link “dialectically-ethically” between Islam and Indonesianness. Maarif has a strong argument, which starts from reading the Koran, history and the Indonesian context that Islam does not need to be placed in “binary opposition” to political realities that have become the nation’s consensus such as Pancasila. Islam in Indonesia must thus be manifested in performance as an “ethical entity” which will later become a pillar for the realization of a civilized Indonesia. Dialectical-ethical thinking can be seen in Maarif’s arguments against democracy which are explored more in this article